Increase the Understanding of University Students on Quadruple Helix and Mosque-Based Economic Empowerment to Boost Potential in Solving Economic Problems - Rakhmawati, Rakhmawati; Yuniawan, Ryan; Akmal, Faiz Maulana; Wibowo, Fahri Hanif Rais; Fatin, Haya Aisyah; Angesti, Fadhilah; Hasibuan, M. Habib Marsan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This activity was organized by the